If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 1 + -5 + 2n Combine like terms: 1 + -5 = -4 6 = -4 + 2n Solving 6 = -4 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 6 + -2n = -4 + 2n + -2n Combine like terms: 2n + -2n = 0 6 + -2n = -4 + 0 6 + -2n = -4 Add '-6' to each side of the equation. 6 + -6 + -2n = -4 + -6 Combine like terms: 6 + -6 = 0 0 + -2n = -4 + -6 -2n = -4 + -6 Combine like terms: -4 + -6 = -10 -2n = -10 Divide each side by '-2'. n = 5 Simplifying n = 5
| X(5x-4)(x+4)=0 | | -7(x+4)-45=8-18 | | -20-y=10 | | 2x+1=-23 | | 56p-8=-16p-32 | | .6=v-2.33 | | (8m-6)(4m+2)= | | 2x-2y=7 | | h/6+h/6=11/6 | | 8x+9x= | | 60+2y=-10 | | -1-2x=-19 | | 7(2x+3)=3 | | 12b-5=3G | | 4y+2x+8=10 | | 10+2y=-10 | | 3z-2+3=-15 | | 6a+2b-11a+4b= | | 4x+25=5x+29 | | 2(2)-2y=7 | | 23x-22x+20=17 | | -5x+20y=20 | | 2m-3= | | -5+20y=20 | | 7x-2=5x+3 | | 8x+1=2x-11 | | 10=b(2*3) | | -5(c+3)+4(c-2)=2(c+2) | | 3+2B=11 | | 16x^2+32+16=81 | | 20+2y=-10 | | 4x+2y+8=10 |